New information on the braincase and inner ear of Euparkeria capensis Broom: implications for diapsid and archosaur evolution - Sobral, Gabriela (R Soc Open Sci, 2016)
Since its discovery, Euparkeria capensis has been a key taxon for understanding the early evolution of archosaurs. The braincase of Euparkeria was described based on a single specimen, but much uncertainty remained. For the first time, all available braincase material of Euparkeria is re-examined using micro-computed tomography scanning. Contrary to previous work, the parabasisphenoid does not form the posterior border of the fenestra ovalis in lateral view, but it does bear a dorsal projection that forms the anteroventral half of the fenestra. No bone pneumatization was found, but the lateral depression of the parabasisphenoid may have been pneumatic. We propose that the lateral depression likely corresponds to the anterior tympanic recess present in crown archosaurs. The presence of a laterosphenoid is confirmed for Euparkeria. It largely conforms to the crocodilian condition, but shows some features which make it more similar to the avemetatarsalian laterosphenoid. The cochlea of Euparkeria is elongated, forming a deep cochlear recess. In comparison with other basal archosauromorphs, the metotic foramen is much enlarged and regionalized into vagus and recessus scalae tympani areas, indicating an increase in its pressure-relief mechanism. The anterior semicircular canal is extended and corresponds to an enlarged floccular fossa. These aspects of the braincase morphology may be related to the development of a more upright posture and active lifestyle. They also indicate further adaptations of the hearing system of Euparkeria to terrestriality.